ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN OUTCOME PASIEN CEDERA KEPALA DI IGD RSUD Prof. Dr. MARGONO SOEKARDJO PURWOKERTO - Putra Agina Widyaswara Suwaryo; Titin Andri Wihastuti; Mukhamad Fathoni (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
Trauma is one of the biggest causes of death in the world. Thousands of people died from trauma each years. Many trauma occur in developing countries or countries with low incomes. The survey carried out showed 90% of trauma occur in developing countries. Outcome head injury patients determined from the initial condition when the patient entered in the ER (Emergency Room). Analysis of the patient's condition will determine the appropriate nursing actions that affect patient outcome. The purpose of this study was to analyze factors associated with outcome head injury patients in ER Prof. Dr. Margono Soekardjo Purwokerto Hospital. This study is a prospective with observational analytic design. The sample in this study amounted to 56 people.The results of Spearman and coefficient contingency indicates that there is a relationship between initial GCS score (p = 0.000) and systolic blood pressure (p = 0.000)with a outcomes of head injury patient. There is no correlation between age (p = 0.478)respiratory rate (p = 0.956) and pulse (.318) with a outcomes of head injury patient. Analysis of logistic regression shows that systolic blood pressure (RR = 6.768) is the dominant factor associated with outcomes of head injury patient. Therefore, the need to improve the management hemodynamic of the patient's, especially blood pressure to prevent bad outcomes. Keywords: outcome, head injury, Emergency Room